Pensamento algébrico: um estudo exploratório com estudantes de Pedagogia - Nascimento, Rosilda Santos do (2020)
The professionals trained in the Pedagogy course, characterized as "multipurpose teachers" are responsible for teaching all the curricular components of elementary school - early years, including the subject of Mathematics. Based on the guidelines present in the National Common Curricular Base (BRASIL, 2017), for this area, one of the Thematic Units corresponds to the teaching of Algebra from the 1st to the 9th year, with defined objectives and skills. Based on Tardif (2002), Pimenta (1999), Curi (2004) and Serrazina (2002), we present the necessary knowledge in teacher education, along with the trajectory and conceptualizations of algebraic thinking through the ideas of Lins and Gimenez (1998) , PCN (1998), Van de Walle (2009), Kaput (2008), Ponte, Branco and Matos (2009), among other authors, who state that thinking algebraically is nothing more than producing meanings for situations in terms of numbers and arithmetic operations with the equalities, inequalities, generalize and perceive regularities. In this circumstance, the present research aimed to analyze the knowledge of students of a Pedagogy course about problem situations involving Algebraic Thinking in the early years of Elementary School. The study has a qualitative approach, as it seeks to interpret the phenomenon of the understanding of algebraic thinking by students of Pedagogy. In addition, this research has an exploratory character, as it aimed to become familiar with a subject that has not been investigated yet. The information was obtained through a questionnaire applied to 29 students in two classes of a Pedagogy course at the Federal University of Paraíba with different profiles. The questionnaire was made up of questions covering the social, academic and professional aspects of the participants, in addition to didactic questions corresponding to the early years of elementary school related to algebra. The information collected was categorized based on the content analysis of Bardin (1979) and analyzed in the light of the theoretical framework on teacher education and Algebraic Thinking. The results indicated that the majority of the participants used arithmetic representations to solve the problem situations covering Algebraic Thinking. Another point was the significant error rate for the solutions to the questions, although all could be solved with arithmetic concepts. Thus, we conclude by highlighting the need to improve basic knowledge of arithmetic for teaching mathematics to students of Pedagogy, which will be the basis for the construction of algebraic concepts.